2014
DOI: 10.2166/wst.2014.328
|View full text |Cite
|
Sign up to set email alerts
|

Cactus juice as bioflocculant in the coagulation–flocculation process for industrial wastewater treatment: a comparative study with polyacrylamide

Abstract: Most industries in the world treat their wastewaters with a conventional coagulation-flocculation process using alum as coagulant, polyacrylamide (PAM) as flocculant and lime as coagulant aid. To reduce the use of chemical products in the process, experiments were conducted to substitute the PAM with cactus juice (CJ) as flocculant. From the obtained data, it was concluded that the substitution of PAM with CJ in the coagulation-flocculation process was very effective, compared with PAM. Depending on the wastew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…A broad peak at 3285 cm −1 was observed, attributed to the absorption of the hydroxyl group (OH) bending to the water molecule. The presence of -COOH, -OH, and -NH 2 functional groups in the polysaccharides-based coagulant made it preferred for aggregation processes [27]. Therefore, all the functional groups observed in Tacca leontopetaloides starch support the capability of starch as the substituted chemical flocculant.…”
Section: Morphologicalmentioning
confidence: 97%
“…A broad peak at 3285 cm −1 was observed, attributed to the absorption of the hydroxyl group (OH) bending to the water molecule. The presence of -COOH, -OH, and -NH 2 functional groups in the polysaccharides-based coagulant made it preferred for aggregation processes [27]. Therefore, all the functional groups observed in Tacca leontopetaloides starch support the capability of starch as the substituted chemical flocculant.…”
Section: Morphologicalmentioning
confidence: 97%
“…With similarity to all biological materials derived from plants, cactus extract effectiveness might be affected over time. It is worth noting that Sellami et al [ 30 ] reported that raw juice had lost significantly its flocculation power within seven days once kept at room temperature. Likewise, De Souza et al [ 60 ] noticed that a storage period of four days at room temperature did not affect cactus extracts coagulation activity, however a drastic change occurred starting from the 5th day when a great loss in turbidity removal was registered.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of storage time on the flocculation performance of the most efficient powder formula were assessed over a period of 8 months. It is worth recalling that the flocculating activity of fresh cactus mucilage is restricted to its shelf life since this material is prone to microbial activity attack due to its considerable water and carbohydrates content [ 30 ]. Hence, producing high quality bio-flocculants with longer longevity is one of the driving forces behind exploring the powdered formulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the chemical method the alum is the mostly used coagulant but it has severe health problems like it causes Alzheimer's diseases (Martyn et al, 1989;Letterman and Pero, 1990), so this water cannot be used to irrigate the fields (Aizawa et al, 1990). Cactus can be used as a coagulant (Sellami et al, 2014). Cactus reduces the turbidity, COD, and heavy metal content in water.…”
Section: Cactus As a Coagulantmentioning
confidence: 99%